2016
DOI: 10.1002/lary.26309
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib enhances the inhibitory effect of 5-FU on human squamous cell carcinoma proliferation by ROS production

Abstract: Objectives The role of celecoxib in preventing and treating tumors has attracted broad attention in recent years because of its selective and specific inhibition of COX‐2 activity. We investigated the inhibitory effects and mechanisms of celecoxib combined with 5‐fluorouracil (5‐FU) on proliferation of squamous cell carcinoma cells in vivo and in vitro. Study Design Animal study and basic research. Methods SNU‐1041 and SNU‐1076 squamous cell lines and an orthotopic tongue cancer mouse model were used to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Also in cutaneous T-cell lymphoma cells, apoptosis induction by indirubin derivatives was ROS-dependent [15]. Induction of ROS in the course of celecoxib treatment has already been reported in melanoma and breast cancer cells [54], and ROS production was suggested as a key mechanism for celecoxib's anticancer activity in combination with 5-FU in head and neck cancer cells [55].…”
Section: Discussionmentioning
confidence: 90%
“…Also in cutaneous T-cell lymphoma cells, apoptosis induction by indirubin derivatives was ROS-dependent [15]. Induction of ROS in the course of celecoxib treatment has already been reported in melanoma and breast cancer cells [54], and ROS production was suggested as a key mechanism for celecoxib's anticancer activity in combination with 5-FU in head and neck cancer cells [55].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies revealed that laryngeal squamous cell carcinoma progression is associated with many signaling pathways, such as the NF-κB signaling pathway, 37 vitamin D receptor signaling pathway, 28 AKT signaling pathway, 27,33,38,39 and Notch2 signaling pathway. 40 Tra2β is involved in the activation of many signaling pathway, such as the Wnt signaling pathway 41 and HtrA/PED pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FU meanwhile interferes with the synthesis of RNA to resist tumors. Moreover, increased ROS cause oxidative damage and then result in the breakage of NMSC cell membrane lipids, proteins, and DNA strand chain [85, 86]. The targeted inhibitors dabrafenib and trametinib were used to treat melanoma and SCC mainly by involving ROS overproduction and caspase-activated apoptosis [87].…”
Section: Treatments For Skin Cancer Targeting Rosmentioning
confidence: 99%